Activation of the PI3K/AKT signalling pathway by insulin-like growth factor type II stimulates metalloproteinase 9 mRNA expression in choriocarcinoma cells (2009)
Metalloproteinases 2 and 9 (MMP-2 and MMP-9) and Tissue Inhibitor-1 of MMPs (TIMP-1) could contribute to regulate the invasive behaviour of trophoblastic cells, effect which could be mediated by Insulin- like growth factor type II (IGF-II), which regulates the development and function of trophoblast at the foetal-maternal interface. The aim of this study was to investigate the role of the PI3K/AKT signalling pathway activated by IGF-II in the expression of MMP-2 and MMP-9 involved in the invasion process in the human choriocarcinoma cell line JEG-3. MMP-2, MMP-9 and TIMP-1mARNexpression in those cells were evaluated by RT-PCR using different IGF-II doses and conditions while signalling pathway was evaluated using Western blot. It was found that IGF-II does not contribute to trophoblastic cells proliferation, however, it promotes mARN expression of MMP-9 and TIMP-1, but not of MMP-2, in a dose-dependent way. The effect on MMP-9 expression is mediated through IGF-II activation of PI3K/AKT signaling pathway after phosphorylation of the IGF-I receptor (IGF-IR). According with the results a model is proposed in which the interaction of IGF-II with IGF-IR leads to PI3K/AKT activation and subsequent expression and activation of MMP-9. This activation is an essential requirement for the invasive process.